Uso da mefs e hidrodestilação no estudo dos compostos orgânicos voláteis da espécie Plectranthus grandis, análise citotóxica e validação de métodos por CG-EM - Camelo, André Luiz Melo (2014)
This work uses the SPME as a complementary technique in the investigation of hydrodistillation of volatile organic compounds from the root, stem and leaves of Plectranthus grandis species, which was used for analysis of gas chromatography. For this, a previous study of the variables that significantly influence the extraction of these volatile, so using the best fiber coating, the best extraction time, temperature and amount of sample was performed. That in order to achieve a safe and reliable analysis. Thus, with the use of SPME and hydrodistillation was identified by gas chromatography / mass spectrometry and linear retention index of 76 compounds distributed in the three parts of the plant. Moreover, the study revealed that SPME extraction was efficient to approximately ¾ of the total number of identified compounds that were effective methodology for making this preliminary analysis, it requires a small amount of sample, a short time interval not used to extract and forms exhaustive for extracting volatile. With this study, it was found that SPME can extract only 20 volatile compounds, leading us to believe that they suffer degradations at the extraction by hydrodistillation. Moreover, the study revealed that the essential oil extracted by hydrodistillation shows percentage inhibition of growth of three human tumor cell lines. The trans - β - caryophyllene was the major compound leaves of this species, as well as the discovery of this stem. Thus, developed and validated a methodology for the analysis of trans - β - caryophyllene, this step, which included a study of efficiency in terms of height of dishes as well as investigating the diffusion of this compound in the stationary phase and mobile phase capillary column.